Understandings of the role of a public library in Estonia - Põldaas, Mai (Qualitative and Quantitative Methods in Libraries, 2017)
The results of the study about the understandings of the role of a public library in Estonia are introduced. It is an empirical study. To carry out the study, qualitative research methods were used. First the documentary analysis of national polices for culture, information and lifelong learning were done by using content analysis. Then various media materials (the articles and interviews of ministers, politicians, library directors, writers and other opinion leaders) were first analysed by using content analysis. Using the categories created during the content analysis, discourse analysis was used to find the discourses there exist in Estonian society about the understandings of public library’s role. The results show, that the public library in Estonia is a book and reading oriented institution. Public libraries in Estonia act as active community centers, especially in rural areas of the country. They are not seen much as educational institutions and it is not expected from them to make different kind of media materials (like music, films) available for the public. Discourse analysis reveals the opposition between information and library worlds, a kind of battle between the new and old understandings. To continue, there a dialog and cooperation is needed between different parties. There is a need for national public library policy in Estonia. It should state, what are the roles of a public library and in which direction do public libraries develop in Estonia.